Standardization of Sowing Time and Leaf Cuttings for Seed Yield and Quality Component of Palak (Beta vulgaris var bengalensis) - VPS PANGHAL; MAKHAN LAL; AXAY BHUKER; DS DUHAN (Seed Research, 2026)
A field study to evaluate the effects of sowing time and leaf cutting on the yield and quality of palak seed was conducted at Vegetable Research Farm of Chaudhary Charan Singh Haryana Agricultural University, Hisar for a period of three years. The treatment comprises four dates of sowing and three levels of leaf cutting. The results revealed that the crop sown on 25thOctober with one cutting had maximum seed yield (20.04 q/ha), 100 seed weight (1.41 g), germination (79.20%)and seed vigour index-1, which was significantly higher than the 10th October and November sown crop. More cuttings though increased the total green leaf yield but the seed yield and quality in terms of germination, test weight and vigour Index-1 were considerably reduced due to less absorption and storage of photosynthates. Thus, the crop was sown on 25th October with one cutting after 30 days of sowing gives maximum seed yield and better quality seed with an additional green leaf yield (18.98 q/ ha)of palak.